2017
DOI: 10.1242/bio.025122
|View full text |Cite
|
Sign up to set email alerts
|

Culture time of vitrified/warmed zygotes before microinjection affects the production efficiency of CRISPR-Cas9-mediated knock-in mice

Abstract: Robust reproductive engineering techniques are required for the efficient and rapid production of genetically modified mice. We have reported the efficient production of genome-edited mice using reproductive engineering techniques, such as ultra-superovulation, in vitro fertilization (IVF) and vitrification/warming of zygotes. We usually use vitrified/warmed fertilized oocytes created by IVF for microinjection because of work efficiency and flexible scheduling. Here, we investigated whether the culture time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Subsequently, the gRNAs were synthesized using a MEGAshortscript T7 Kit (Thermo Fisher Scientific, Tokyo, Japan), and then purified with a MEGAclear Kit (Thermo Fisher Scientific). The gRNA designs of interleukin-11 (Il11), tyrosinase ( Tyr ), and secreted phosphoprotein 1 ( Spp1 ) genes were as described previously [ 20 , 21 ]. In the generation of Il11 mutant mice, gRNA B was synthesized and used as shown in a previous report.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the gRNAs were synthesized using a MEGAshortscript T7 Kit (Thermo Fisher Scientific, Tokyo, Japan), and then purified with a MEGAclear Kit (Thermo Fisher Scientific). The gRNA designs of interleukin-11 (Il11), tyrosinase ( Tyr ), and secreted phosphoprotein 1 ( Spp1 ) genes were as described previously [ 20 , 21 ]. In the generation of Il11 mutant mice, gRNA B was synthesized and used as shown in a previous report.…”
Section: Methodsmentioning
confidence: 99%
“…Cas9 Nuclease 3NLS; Tokyo, Japan). The sequence of ssODN for three-base substitution at the Spp1 locus was the same as in previous reports [ 20 , 21 ]. ssODN was synthesized by Integrated DNA Technologies (Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the detailed protocol, freely available materials, and online design tool for the CRISPR-mediated PITCh knock-in were provided by the authors Nakamae et al 2017). Along with these user-friendly resources, the application examples of CRISPR-mediated PITCh have become more diversified, e.g., high-throughput epitope tagging in cultured cells for chromatin immunoprecipitation (ChIP)-seq (Xiong et al 2017), the application in mammalian zygotes (Aida et al 2016;Nakagawa et al 2017), and in vivo somatic knock-in in mice (Yao et al 2017a) were reported one after another. Note that recent design of CRISPR-mediated PITCh has employed longer microhomologies (~40 bp); thus, it might be based on SSA rather than MMEJ.…”
Section: Mmej/ssa-mediated Gene Knock-inmentioning
confidence: 99%